The clinical characteristics and quality of life of 248 pediatric and adult patients with Congenital Adrenal Hyperplasia - Shafaay, Edi A.; Aldriweesh, Mohammed A.; Aljahdali, Ghadeer L.; Babiker, Amir; Alomar, Abdulrahman O.; Alharbi, Khulood M.; Aldalaan, Haneen; Alenazi, Ahmed; Alangari, Abdulaziz S.; Alsagheir, Afaf; Adriaansen, Bas P. H.; Claahsen – van der Grinten, Hedi L.; et al. (Frontiers in Endocrinology, 2023)
Background: Congenital Adrenal Hyperplasia (CAH) is a chronic disease that requires lifelong treatment. Patients may face stigmatization, which may affect their quality of life (QoL). Therefore, we assessed the clinical characteristics and QoL of patients with CAH in the Middle East. Methods: This case-control study included patients with CAH aged >5 years from two tertiary centers (2020–2021). The patients were matched to a healthy control group and were then divided into pediatric and adult groups. Data were collected from their electronic medical records. Additionally, the EQ-5D-5L QoL questionnaire was completed by both the patients and control group to assess five domains (mobility, self-care, usual activities, pain/discomfort, and anxiety/depression). Results: The study included 248 patients with CAH (females: 58.8%), with a family history of the condition (57.3%) and/or parental consanguinity (68.1%). The most frequently reported gene defect was CYP21A2, while the most commonly reported symptoms/signs were ambiguous genitalia and obesity. Almost all female patients had received corrective surgery. The questionnaire response rate was 86.3% (n=214/248). The CAH patient group’s mean total QoL score was 85.2 compared with 99.8 in the control. Further, CAH patients had lower QoL scores in all domains compared to those in the control group (p ≤ 0.0001–0.0023). The pain/discomfort and anxiety/depression domains were affected significantly more than the other domains were, with 47.7% and 44.4% participants, respectively, p<0.0001. Additionally, obesity was found to be a predictor of reduced mobility following a logistic regression analysis (p ≤ 0.04, OR (0.18-0.98)). Conclusion: Patients with CAH reported lower QoL overall, particularly in the pain/discomfort and anxiety/depression domains. Based on this, we recommend the early involvement of psychologists in a multidisciplinary team approach, pre-marital screening, and the implementation of awareness programs for people diagnosed with CAH in communities with high consanguineous mating.